A Comparative Study of the Effect of MgO and CaCO3 as Support Materials in the Synthesis of Carbon Nanotubes with Fe/Co as Catalyst - Ezekiel D. Dikio; Albert J. Kupeta; Force T. Thema (Journal of Chemistry)
A comparative study of the effect of magnesium oxide and calcium carbonate as support material in the synthesis of carbon nanotubes using the catalyst Fe/Co is presented. The synthesized carbon nanotubes were characterized with Raman spectroscopy, scanning electron spectroscopy (SEM), high-resolution transmission electron microscopy (HRTEM), X-ray diffraction spectroscopy (XRD), and energy dispersive spectroscopy (EDS). The morphology of the carbon nanotubes synthesized with magnesium oxide as support material gives rise to carbon nanotubes with consistent and well-defined structure unlike that synthesized with calcium carbonate. The ID/IG ratio of synthesized carbon nanotubes (CNTs) was 0.8544 for magnesium oxide supported compared to 0.8501 for calcium carbonate supported carbon nanotube.